Effectiveness and impact of the 4CMenB vaccine against invasive serogroup B meningococcal disease and gonorrhoea in an infant, child, and adolescent programme: an observational cohort and case-control study. Issue 7 (July 2022) - Wang, Bing; Giles, Lynne; Andraweera, Prabha; McMillan, Mark; Almond, Sara; Beazley, Rebecca; Mitchell, Janine; Lally, Noel; Ahoure, Michele; Denehy, Emma; Koehler, Ann; Flood, Louise; et al.
Summary: Background: A programme of vaccination with the four-component serogroup B meningococcal (4CMenB) vaccine was introduced in South Australia for infants and children aged 0–3 years on Oct 1, 2018, and for senior school students in school years 10 and 11 (aged 15–16 years) and young adults aged 17–20 years on Feb 1, 2019. We aimed to evaluate vaccine effectiveness and impact on serogroup B meningococcal disease and gonorrhoea 2 years after implementation of the programme. Methods: We did a cohort and case-control study among those targeted by the South Australia 4CMenB vaccination programme. We obtained disease notification data from SA Health, Government of South Australia, and vaccine coverage data from the South Australian records of the Australian Immunisation Register. Vaccine effectiveness was estimated as the reduction in the odds of infection using the screening and case-control methods. Vaccine impact was estimated as incidence rate ratios (IRRs), obtained by comparing case numbers in each year following the start of the vaccination programme with cases in the equivalent age cohort during the pre-vaccination programme years. We used Poisson or negative binomial models, as appropriate, with adjustment for changes in the incidence of serogroup B meningococcal disease in age cohorts not eligible for vaccination through the state programme. Findings: 4CMenB vaccine coverage 2 years after introduction of the childhood vaccination programme was 94·9% (33 357 of 35 144 eligible individuals) for one dose, 91·4% (26 443 of 28 922) for two doses, and 79·4% (15 440 of 19 436) for three doses in infants. The one-dose (77·1%, 16 422 of 21 305) and two-dose (69·0%, 14 704 of 21 305) coverage was highest in adolescents born in 2003 (approximately year 10 students). 2 years after implementation of the childhood vaccination programme, incidence of serogroup B meningococcal disease was significantly reduced compared with before programme implementation in infants aged 12 weeks to 11 months (adjusted IRR [aIRR] 0·40 [95% CI 0·23–0·69], p=0·0011), but not in those aged 1 year (0·79 [0·16–3·87], p=0·77), 2 years (0·75 [0·18–3·14], p=0·70), or 4 years (3·00 [0·47–18·79], p=0·24). aIRRs were not calculable in those aged 3 or 5 years because of no cases occurring after programme implementation. aIRR for serogroup B meningococcal disease was 0·27 (0·06–1·16, p=0·078) in adolescents aged 15–18 years 2 years after implementation of the adolescent and young adult programme, and 1·20 (0·70–2·06, p=0·51) in those aged 19–21 years in the first year. Two-dose vaccine effectiveness against serogroup B meningococcal disease was estimated to be 94·2% (95% CI 36·6–99·5) using the screening method and 94·7% (40·3–99·5) using the case-control method in children, and 100% in adolescents and young adults (no cases reported after implementation). Estimated two-dose vaccine effectiveness against gonorrhoea in adolescents and young adults was 32·7% (8·3–50·6) based on the case-control method using age-matched individuals with chlamydia infection as controls. Interpretation: 4CMenB vaccine shows sustained effectiveness against serogroup B meningococcal disease 2 years after introduction in infants and adolescents, and moderate effectiveness against gonorrhoea in adolescents. The high vaccine effectiveness against serogroup B meningococcal disease is likely due to high coverage in the target age groups and close antigenic match between the 4CMenB vaccine and the disease-associated serogroup B meningococcal strains circulating in South Australia. COVID-19-related physical distancing policies might have contributed to further declines in serogroup B meningococcal disease cases during the programme's second year. Funding: SA Health, Government of South Australia.